Penalty or premium for foreign ownership in Thailand? Comparing public support for waste-to-energy plants operated by Thai, Japanese, and Chinese Companies - Azusa Uji; Jaehyun Song; Nives Dolšak; Aseem Prakash (PLoS ONE, 2025)
Waste-to-energy (WtE) projects use municipal waste to generate energy. While they increase local environmental and health risks, they also generate local environmental and economic benefits. If facility operator characteristics influence perceptions of risks and benefits, does public support for a WtE facility change if it is operated by a foreign firm? Using a survey experiment in Thailand (n = 829), we examine support for a hypothetical WtE plant operated by local Thai (reference category), Japanese (treatment 1), and Chinese (treatment 2) firms. We find that while respondents are less supportive of WtE plants operated by Chinese companies (“penalty for foreignness”), their support does not change for Japanese plants (neither penalty nor premium for foreignness). Importantly, while perceptions of local economic benefits increase support, perceptions of environmental benefits from reducing waste and landfills do not. Respondents support WtE plants when their communities experience air pollution from coal-fired power plants and when they support the Thai government’s decision to ban the manufacturing and sale of single-use plastics.